Indonesian Ulema Council Fatwa on Boycotting Products Supporting Israel in the Ijtihad Discourse of Nahdatul Ulama and Muhammadiyah - Giyarsi; Iim Fahimah; Miti Yarmunida (Islamic Research Publiser, 2023)
This study aims to determine the legal provisions of boycotting Israeli products in the perspective of Ijtihad Nahdhatul Ulama and Muhammadiyah. The method used is a descriptive-analytical method with a qualitative approach. The source of this research data comes from litelature studies. Data analysis is carried out through the process of inventory, classification, and data analysis. The results of this study are: 1) the boycott law of Israeli products in the concept of ijtihad NU is mandatory if it is believed and known that profits from the sale of such products by Israel are used to help launch attacks against Palestinians. However, if it is not believed and it is not known for certain that the profits obtained from the sale of these products are to help fight the Palestinians, then buying Israeli products is not obligatory but makhruh because in a war situation that allows the use of profits for war; 2) In the concept of Muhammadiyah ijtihad, boycotting Israeli products becomes fardhu 'ain for Palestinians and fardhu kifayah for Muslims in other countries. Likewise, the law of boycotting products from branch companies and parties that clearly support Israel is mandatory, while boycotting products from local shops and hawkers is discouraged because it results in greater madharat. So that compliance with the MUI Fatwa related to boycotting Israeli products must be adjusted to the situation and conditions.